Wave interaction with multiple wavy porous barriers using dual boundary element method. (January 2021) - Vijay, K.G.; Nishad, Chandra Shekhar; Neelamani, S.; Sahoo, T.
Highlights: Gravity wave interaction with multiple wavy porous barriers is studied. A quadratic pressure drop is adopted for waves past the porous barriers. The numerical model is based on an iterative Dual boundary element method (DBEM). Bragg reflection is observed when the porosity of the multiple barriers is zero. Increase in the number of porous plates, ripple amplitude and number of ripples reduces the wave transmission appreciably. The proposed breakwater progressively dissipates the wave energy without increasing the hydrodynamic loads. Abstract: The gravity wave interaction with horizontally staggered multiple thin wavy porous barriers is analyzed under the assumption of potential flow theory. The dual boundary element method (DBEM) is used to solve the boundary value problem. The accuracy and reliability of the DBEM solutions are ascertained by comparing with known results in the literature and with an independently developed multi-domain boundary element method (MBEM) code. The study is focused on the scattering coefficients and vertical forces on an array of wavy barriers. The numerical results demonstrate that wave transmission by a horizontally staggered porous barrier is much better compared to a single horizontal plate. It is recommended to use plate porosity of 0.05 to 0.20, if transmission coefficient of less than 0.50 is needed, especially for relative water depth k 0 h > 2. With an increase in the number of ripples and ripple amplitude on the porous plates, it is possible to further reduce wave transmission by 5% to 10%. Also, an increase in the inclination of the plate from 0 to 10 degrees can reduce the wave transmission and increases the wave reflection to 5% to 10%. Further, a reduction of about 10% to 30% in the vertical force on the wavy plate is possible for k 0 h ≥ 1 with an increase in the relative ripple amplitude, the number of ripples and increased plate rotation. This essentially will help in the reduction of pile penetration length into the sea bed soil. The results of the present study can be used for the optimal design of wavy plate as a wave barrier for offshore and coastal engineering applications.